2023
DOI: 10.21083/978-1-77470-038-9
|View full text |Cite
|
Sign up to set email alerts
|

Urban Groundwater

Abstract: The GROUNDWATER PROJECT ©The Author(s) Free download from gw-project.orgAnyone may use and share gw-project.org links. Direct distribution of the book is strictly prohibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 220 publications
0
4
0
Order By: Relevance
“…The physicochemical parameters are characterised by different sources that influence their values, and at the same time, several processes normally affect the physicochemical values of groundwater [1]. Previous studies have confirmed the relevant role of natural processes, such as climate change [2,3], geological features [4], microbiological features [5] and anthropogenic processes [6], in modifying groundwater quality. The impacts of climate change have been extensively addressed [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physicochemical parameters are characterised by different sources that influence their values, and at the same time, several processes normally affect the physicochemical values of groundwater [1]. Previous studies have confirmed the relevant role of natural processes, such as climate change [2,3], geological features [4], microbiological features [5] and anthropogenic processes [6], in modifying groundwater quality. The impacts of climate change have been extensively addressed [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A number of documented global groundwater contaminant challenges related to the use of large quantities of agrochemical components have been reported for anthropogenic processes. The anthropogenic pressures influencing the groundwater chemistry are countless [6]. In particular, extensive irrigation represents a relevant recharge that can induce the dilution or concentration of NO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge equips us to tackle pressing environmental issues, such as water scarcity and pollution. Moreover, the findings obtained from hydrogeological research are indispensable for informed decision making across a multitude of domains, including urban planning, engineering construction, and agricultural production [10]. In this way, it not only concerns the safeguarding and sustainable development of the natural environment, but also directly impacts the economic prosperity and security of human society.…”
mentioning
confidence: 99%
“…Urban Groundwater (Howard 2023) is a masterful and timely compilation that provides the base for needed future research on and management solutions to urban water and, specifically, groundwater issues. The author's 40‐plus years of global research experience and his long service as Co‐Director of the International Association of Hydrogeologists' Urban Groundwater Network make him the ideal author for this volume.…”
mentioning
confidence: 99%